Nanoparticles in the clinic: An update - Aaron C. Anselmo; Samir Mitragotri (Wiley, 2019)
Abstract Nanoparticle drug delivery systems have been used in the clinic since the early 1990's. Since that time, the field of nanomedicine has evolved alongside growing technological needs to improve the delivery of various therapeutics. Over these past decades, newer generations of nanoparticles have emerged that are capable of performing additional delivery functions that can enable treatment via new therapeutic modalities. In the current clinical landscape, many of these new generation nanoparticles have reached clinical trials and have been approved for various indications. In the first issue of Bioengineering & Translational Medicine in 2016, we reviewed the history, current clinical landscape, and clinical challenges of nanoparticle delivery systems. Here, we provide a 3 year update on the current clinical landscape of nanoparticle drug delivery systems and highlight newly approved nanomedicines, provide a status update on previous clinical trials, and highlight new technologies that have recently entered the clinic.